2021
DOI: 10.5194/tc-2021-344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the role of snow metamorphism on the isotopic composition of the surface snow at EastGRIP

Abstract: Abstract. Stable water isotopes from polar ice cores are invaluable high-resolution climate proxy records. Recent studies have aimed to improve knowledge of how the climate signal is stored in the water isotope record by addressing the influence of post-depositional processes on the surface snow isotopic composition. In this study, the relationship between changes in surface snow microstructure after precipitation/deposition events and water isotopes is explored using measurements of snow specific surface area… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…For the period between 3 and 17 July, Harris Stuart et al. (2021) analyzed a different isotope data set from the same study site and found a decrease in d‐excess without changes in δ 18 O, similar to our observations (Figure S2 in Supporting Information S1). They also report two SSA decrease events during this period potentially related to post‐depositional processes, such as vapor‐snow exchange.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…For the period between 3 and 17 July, Harris Stuart et al. (2021) analyzed a different isotope data set from the same study site and found a decrease in d‐excess without changes in δ 18 O, similar to our observations (Figure S2 in Supporting Information S1). They also report two SSA decrease events during this period potentially related to post‐depositional processes, such as vapor‐snow exchange.…”
Section: Discussionsupporting
confidence: 88%
“…Environmental conditions during our observation period were analyzed and described in Harris Stuart et al. (2021), Wahl et al. (2021), and Wahl et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations